2021
DOI: 10.15294/lc.v15i2.28135
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging in International Student Teaching: Narratives of Filipino Teachers in an Indonesian Setting

Abstract: Regardless of numerous studies on translanguaging, little attention has been given to its practice among pre-service teachers, particularly in the ASEAN context. To fill this gap, this article explores the experiences of three pre-service English teachers from the Philippines who were assigned to a private elementary school in Indonesia as part of a pre-service teacher exchange program. Working in a context that did not share a similar first or second language, the three teachers used English, their second lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…These findings can be further substantiated by the empirical evidence that Indonesian teachers have high technological, pedagogical, and content knowledge competence (Maknun, 2022); even in the Philippines, teachers showed very high digital competence (Galaraga & Reynato, 2022). Furthermore, Filipino teachers were found to have the ability to communicate in a second language proficiently and effectively (Prasetya, 2021;Mangila, 2018;Ozaki, 2021).…”
Section: Teaching Competencementioning
confidence: 80%
See 1 more Smart Citation
“…These findings can be further substantiated by the empirical evidence that Indonesian teachers have high technological, pedagogical, and content knowledge competence (Maknun, 2022); even in the Philippines, teachers showed very high digital competence (Galaraga & Reynato, 2022). Furthermore, Filipino teachers were found to have the ability to communicate in a second language proficiently and effectively (Prasetya, 2021;Mangila, 2018;Ozaki, 2021).…”
Section: Teaching Competencementioning
confidence: 80%
“…Communicating proficiently in a second language is another aspect of instrumental competence. Studies by Prasetya (2021), Mangila (2018), andOzaki (2021) emphasized the proficiency of Filipino teachers in communicating in a second language. This competence enables teachers to engage with students and create inclusive learning environments effectively.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Translation was helpful for helping pre-service teachers delivering materials in ITP, especially if teachers and students do not share the similar language (Prasetya, 2021). In addition to providing translation, she was also accompanied by her supervisor to support her for what she could not do in class.…”
Section: Emotions and Social Interactionsmentioning
confidence: 99%
“…The growing body of research conducted in various contexts of ITP has demonstrated that pre-service English teachers underwent transformation in various aspects, including professional development (Kabilan, 2013;Ateskan, 2016), identities (Kong, 2017), and language use (Prasetya, 2021). In addition to the above-mentioned aspects, another aspect in ITP that has recently gained more attention is emotions.…”
Section: Introductionmentioning
confidence: 99%